Risk of liver cancer among US male veterans with cirrhosis, 1969–1996 - Persson, E C (Nature Publishing Group, 2012)
BACKGROUND: Liver cancer incidence rates in the United States have increased for several decades for reasons that are not entirely clear. Regardless of aetiology, cirrhosis is a strong risk factor for liver cancer. As mortality from cirrhosis has been declining in recent decades, it is possible that the risk of liver cancer among persons with cirrhosis has been affected. METHODS: Data from the US Veterans Affairs medical records database were analysed after adjustment for attained age, race, number of hospital visits, obesity, diabetes, and chronic obstructive pulmonary disease. Hazard ratio (HR) and 95% confidence interval (95% CI) were calculated using Cox proportional hazards modelling. Survival analyses were conducted using age as the time metric and incidence of cirrhosis as a time-dependent covariate. RESULTS: Among 103 257 men with incident cirrhosis, 788 liver cancers developed. The HR of liver cancer was highest among men with viral-related cirrhosis (HR=37.59, 95% CI: 22.57–62.61), lowest among men with alcohol-related cirrhosis (HR=8.20, 95% CI: 7.55–8.91) and intermediate among men with idiopathic cirrhosis (HR=10.45, 95% CI: 8.52–12.81), when compared with those without cirrhosis. Regardless of cirrhosis type, white men had higher HRs than black men. The HR of developing liver cancer increased from 6.40 (95% CI: 4.40–9.33) in 1969–1973 to 34.71 (95% CI: 23.10–52.16) in 1992–1996 for those with cirrhosis compared with those without. CONCLUSION: In conclusion, the significantly increased HR of developing liver cancer among men with cirrhosis compared with men without cirrhosis in the United States may be contributing to the increasing incidence of liver cancer.